1988/89 ネン カキ ナンキョク キングジョージ トウ チョウジョウ キチ デノ ニッチュウ キョウドウ カンソク - 渡辺, 研太郎; ワタナベ, ケンタロウ; 井上, 正鉄; イノウエ, マサカネ; 大山, 佳邦; オオヤマ, ヨシクニ; Watanabe, Kentaro; Inoue, Masakane; Ohyama, Yoshikuni (1990)
P(論文) 昭和63年度から3ヵ年計画で中国南極観測隊との共同観測が"大陸性南極と海洋性南極における動植物相の比較研究"のテーマで開始された。その初年度として1988/89年, 第5次中国南極観測隊(CHINARE-5)に参加し, 11月中旬から約4ヵ月間, 長城基地周辺域で地衣類を中心とした陸上生物および微細藻類を中心とした海洋生物の野外調査を実施した。陸上生物調査はフィルデス半島, バートン半島およびネルソン島で行い, 地衣類については64属199種を識別した。その種数と種組成は昭和基地周辺と非常に異なっている。一方, 海洋生物調査は長城基地前の小湾内から外にかけて5定点を設け, 各層海水中のクロロフィル濃度, 栄養塩, 表面水温等を測定し, プランクトンネット等により種組成研究用標本を採集した。 As the China-Japan collaborative research program on Antarctic biology, 1988-1991,two Japanese biologists carried out field observations and samplings near Great Wall Station (62°13′S, 58°58′W) in King George Island from mid-November 1988 to early March 1989 with the Fifth Chinese National Antarctic Research Expedition (CHINARE-5) members. One of the authors, a lichenologist surveyed the vegetations in the Fildes Peninsula, the Burton Peninsula and Nelson Island and collected lichen specimens for taxonomical works in his laboratory. He recognized 199 taxa of 64 genera tentatively from the area. Another author took part in marine biological observations at five locations in the coastal area off Great Wall Station and collected ice algae and phytoplankton specimens departmental bulletin paper